Developing an Energy Efficient and Sustainable IoT-Enabled Indoor-Air Cooling System Using Earthen Materials - Das, Ananya; Moulick, Sanjib; Debdas, Subhra (Engineering, Technology & Applied Science Research, 2025)
This research focuses on the development of an energy-efficient and sustainable Internet of Things (IoT)-enabled system for indoor air cooling in residential buildings. The system incorporates an earthen air-cooling unit designed from locally sourced clay, leveraging the natural evaporative cooling properties of earthen materials. To identify the best-suited clay for the cooling process, soil samples are collected and tested from three locations in Bhubaneswar, Odisha. The components of the system are crafted by local potters and kiln-fired at 900 °C for durability and functionality. The air-cooling unit design is optimized through Computational Fluid Dynamics (CFD) simulations for maximum temperature reduction by combining evaporative cooling and the Venturi effect. Integrated IoT sensors and controllers enable real-time monitoring and remote control, ensuring energy-efficient operation and consistent indoor cooling. Testing the system in a residential setting in Bhubaneswar suggests a maximum indoor temperature reduction to 24 °C, while consuming 72% less energy than the traditional desert air coolers. This research highlights the potential of combining traditional earthen materials with the modern IoT technology to create a sustainable and energy-efficient solution for indoor air cooling.